2015
DOI: 10.17795/jjnpp-29153
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle and Mean Inactivation Dose of Human Intestinal Colon Cancer HT-29 Cells

Abstract: Background: Mean inactivation dose is a useful radiobiological parameter for the comparison of human cell survival curves. Objectives: Given the importance and accuracy of these parameters, in the present study, the radio sensitivity enhancement of colon cancer (HT-29) cells in the presence of gold nanoparticles (GNPs) were studied using the mean inactivation dose (MID). Materials and Methods: Naked-GNPs with 50 nm diameters were incubated with HT-29 cells. The cytotoxicity and uptake of these particles on HT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Briefly, the cells were incubated with MTT solution (5 mg/mL) for 4 hours, and then, the optical density (OD) was recorded at 570 nm in a 96‐well plate reader (Bio‐Rad). The survival fraction was calculated by the following equation 50,51 : Survival fraction=Mean0.25emOD0.25emin test wellsMean0.25emOD0.25emin cellfree wellsMean0.25emOD0.25emin control wellsMean0.25emOD0.25emin cellfree wells …”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the cells were incubated with MTT solution (5 mg/mL) for 4 hours, and then, the optical density (OD) was recorded at 570 nm in a 96‐well plate reader (Bio‐Rad). The survival fraction was calculated by the following equation 50,51 : Survival fraction=Mean0.25emOD0.25emin test wellsMean0.25emOD0.25emin cellfree wellsMean0.25emOD0.25emin control wellsMean0.25emOD0.25emin cellfree wells …”
Section: Methodsmentioning
confidence: 99%
“…In this regards, Arab-Bafrani et al, in a similar survey, showed that cell survival in the presence of GNPs was more than 90% and the maximum uptake of GNPs was observed at 60 μM concentration of GNP. 25 In our survey based on the WST-1 results, we observe minimal cell toxicity against HT-29 cells at the concentration of 70 µM GNP-F.…”
Section: Resultsmentioning
confidence: 69%
“…Many studies based on several assays demonstrated that the use of GNPs in the presence of orthovoltage (kV) and mega-voltage (MV) radiation had radiosensitization effects. 13,[23][24][25] A c c e p t e d M a n u s c r i p t…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate drug resistance ability, both spheroids (keratin and collagen) and parental cells were singled out using a pipette and seeded in six‐well plates and then incubated with 2, 5, and 10 mM of valproic acid (VPC) . For radiosensitivity assay, cells were irradiated with 2, 4, and 8 Gy X‐rays (6 MV) according to previous reports . Cell viability was evaluated using the MTS assay, the Cell Titer 96 AQueous One Solution Cell Proliferation (ProMega), 48 h after treatment.…”
Section: Methodsmentioning
confidence: 99%